Yoga therapy attenuates the progression of diabetes - insights from proteomics and metabolomics analysis - Sonwane, Babasaheb P.; Raut, Pooja; Chitalkar, Jyotsna; Godbole, Smita; Sabnis, Shanta; Gupta, Jyoti; Santhakumari, B.; Deshpande, Mukund V.; Kulkarni, Mahesh J. (International Journal of Yoga, 2024)
<p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Objective: Diabetes management remains challenging despite advancements in therapeutics, with many subjects developing complications. Yoga has been shown to aid diabetes management. This study investigates the impact of yoga therapy on diabetes progression, utilizing proteomics and metabolomics analyses to explore underlying molecular mechanisms. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Methodology: A 3-month longitudinal study involving healthy subjects with prediabetes and diabetes was conducted. Blood glucose, glycated hemoglobin (HbA1c), lipid profile, and malondialdehyde (MDA) levels were measured before and after the yoga intervention. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Results and conclusion: Healthy subjects showed no significant changes in blood glucose, lipid profile, HbA1c, or MDA levels. However, subjects with prediabetes and diabetes experienced positive changes, with decreases in HbA1c and MDA levels. Proteomics and metabolomics analyses provided insights into the molecular mechanisms by which yoga attenuates diabetes progression in subjects with prediabetes and diabetes. This study is a pioneering effort to understand the molecular basis of yoga's beneficial effects on diabetes management.